O Ensino da educação ambiental e os PCN e DCNEM: Concepções e práticas dos professores de ciências do ensino médio - Pinho, Glauciane Camelo (2017)
Environmental Education (EA) plays a fundamental role in the process of building society committed to transforming man's relationship with nature. National Curricular Parameters (NCPs) place EA as a cross-cutting theme, and therefore EA does not integrate a specific curriculum discipline, and should be worked on by all curricular components and with different types of approaches. The National Curriculum Guidelines for Secondary Education (DCNEM), as well as NCPs, also guide environmental issues to be addressed with a focus on contextualization and interdisciplinarity. Thus, the present research had the purpose of analyzing the conception and practice of the High School Science Teachers of three schools of the state public network of Fortaleza-Ceará, on Teaching AE, in light of the guidelines contained in the NCPs and the DCNEM. The methodology of the research was descriptive in nature, with a case study feature and qualitative approach. The subjects of the research were composed of three teachers from each of the surveyed schools, that is, nine teachers, each consisting of a professor of Chemistry, one of Physics and another of Biology, in addition to a total of one Hundred and three students of the second year of high school. The research technique used was the application of questionnaires and semi-structured interviews to evaluate the personal data, academic training and pedagogical practice of teachers. For students, questionnaires on personal data and their perceptions about the EA practiced by teachers were also applied. Through the results found, it can be concluded that the majority of teachers know the recommendations contained in NCPs and DCNEM for AE. However, they do not incorporate the recommendations of the same ones in the conduction of their disciplines, realizing their practices of superficial way, in the majority of the times only the examples linked to the contents of their disciplines and, therefore, they do not develop A practice that has relation with the orientations. Students confirm that their teachers work on environmental issues in isolation and only in specific situations.